ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Hasanah, Neneng (Universitas Sam Ratulangi, 2020)
The purpose of this study is to analyze the influence of leverage, company size, and profitability on the disclosure of corporate social responsibility of public firms of textiles and garment that listed in the Indonesia Stock Exchange over 2016 until 2018. The independent variables of this study are leverage, company size, and profitability while the dependent variable is the Corporate Social Responsibility (CSR) disclosure. This study conducts logistic regression analysis on 45 public firms of textiles and garment that taken by purposive sampling method. The results of this study show that: (1) leverage significantly effect on corporate social responsibility disclosure; (2) company size insignificant on corporate social responsibility disclosure; and (3) profitability significantly effect on corporate social responsibility disclosure.